Design of Electronic Worksheets Integrated with Problem Based Learning and Ethnoscience to Improve Critical Thinking Skills of High School Students - Herli Gusmita Utami; Emiliannur Emiliannur (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
The rapid advancements in science and technology in the 21st century necessitate significant improvements in the quality of education, especially in fostering students' critical thinking skills. These skills are crucial in the study of physics, as they encompass logical reasoning that can be substantiated. However, current assessments reveal that students' critical thinking abilities are notably lacking, with an average test score of only 46. 78, categorizing them as low performers. This shortfall can largely be attributed to passive learning methods and teaching materials that fail to align with students' learning styles. To tackle this issue, it is essential to develop teaching materials that promote critical thinking. One promising approach is the creation of electronic-based student worksheets that incorporate the Problem-Based Learning (PBL) model alongside an ethnoscience perspective. The PBL model encourages students to actively engage in analyzing problems systematically, while the ethnoscience approach integrates local wisdom into the learning process, making it more relevant and meaningful. This innovative combination aims to transform E-Student Worksheets into a powerful tool for enhancing student engagement and boosting critical thinking skills.